More than a thought experiment : conceptualizing and implementing an Urban Living Lab - Klautzer, Lisa; Hong, Seo Yeon; Narayan, Rumy (IOP Publishing, 2020)
In the context of growing urbanization,1 cities are focal points of social interactions. Embedded in bi-directional feedback loops with wider regional environments and the global ecosystem, cities present, simultaneously, ideal reference points and vital arenas for generating debates about and testing pathways toward emerging sustainable models of livability and a redefined prosperity. The latter no longer limited to mainstream economic definitions but encompassing a more holistic societal prosperity, nurtured by shared experiences, enhanced knowledge generation and exchange, eclectic encounters and ample space for creative expression. The paper presents the conceptual development of an Urban Living Lab (ULL). It employs existing literature on ULL to enable a basic frame of reference, draws on the concept of contextual logic and a philosophical understanding of flow to inform processes for rolling out such a multi-stakeholder engagement experiment. The paper attempts to conceptualize an approach that employs community participation to define contours of a socially inclusive and livable society. This approach aims at empowering networks for transitioning towards such a society within a specific context.
Keywords: Strategic management